2021
DOI: 10.1002/ccd.29733
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of the Hydra self‐expanding transcatheter aortic valve: 6 month results from the GENESIS trial

Abstract: Objectives To evaluate the safety and performance of the Hydra transcatheter aortic valve (THV) in the treatment of symptomatic severe aortic stenosis in patients at high or extreme surgical risk. Background The Hydra THV (Vascular Innovations Co. Ltd., Nonthaburi, Thailand) is a novel flexible repositionable self‐expanding system with supra‐annular bovine pericardial leaflets, available in three sizes, covering aortic annuli between 17 and 27 mm. Methods The GENESIS trial was a prospective, multi‐center, sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…However, RHD among TAVI candidates may increase in significance in the forthcoming years as a consequence of expansion of TAVI to younger patients and immigration from low-income and middle-income countries20; most importantly, however, RHD will come to the spotlight with dissemination of TAVI to middle-income countries 21. Affordable transcatheter heart valves (THV) developed in emerging countries22 23 may open the door to this technology for the rest of the world24 and catalyse the expansion of TAVI to patients with RHD.…”
Section: Discussionmentioning
confidence: 99%
“…However, RHD among TAVI candidates may increase in significance in the forthcoming years as a consequence of expansion of TAVI to younger patients and immigration from low-income and middle-income countries20; most importantly, however, RHD will come to the spotlight with dissemination of TAVI to middle-income countries 21. Affordable transcatheter heart valves (THV) developed in emerging countries22 23 may open the door to this technology for the rest of the world24 and catalyse the expansion of TAVI to patients with RHD.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lower radial strength may lead to less mechanical injury to the conduction system and explain the lower rate for a PPM implantation (from 8.3 to 12.3%9) [27][28][29] compared to the reported PPM following the implantation of other SE THVs (17.4% to 34.1%) [32,33]. On the other hand, the low radial force may translate into incomplete apposition of the device to the virtual basal ring, increasing the risk of PVL [19]. However, data from observational site-reported studies showed an incidence of moderate-to-severe PVL ranging from 1.4% to 4.8% [33][34][35].…”
Section: Acurate Neo™mentioning
confidence: 99%
“…Both the delivery and the loading system were the same for all three THV sizes. The GENESIS trial [19] assessed the performance of the SE Hydra THV system in patients with severe AS and high or extreme surgical risk. In this trial, VARC-2 defined device success was 92.5%.…”
Section: Self-expanding Transcatheter Heart Valvesmentioning
confidence: 99%
“…Fifteen registries and studies reported procedural success [16][17][18][19][21][22][23][24][25][26]28,29,[32][33][34]. The mean success rate was 95.40% with a weighted standard deviation (SD) of 1.5% [16][17][18][19][21][22][23][24][25][26]28,29,[32][33][34].…”
Section: Procedural Successmentioning
confidence: 99%
“…Eighteen studies reported that a total of 224 out of 13,509 patients died by 30 days after TAVI, giving a weighted mean for 30-day mortality rate of 1.66%, with a weighted standard deviation of 1.2% [8,[17][18][19][20][21][22][23][24][25][26][28][29][30][31][32][33].…”
Section: -Day Mortalitymentioning
confidence: 99%